Effects of word list length during episodic memory encoding observation by the event-related potential and time-frequency - Veliks, Viktors; Kolesovs, Aleksandrs; Porozovs, Juris; Igonins, Dmitrijs (Frontiers in Human Neuroscience, 2025)
The present study explored the effects of word list length during the encoding of visual verbal stimuli. The participants received Latvian nouns in lists of different lengths: short (up to 29), medium (30–59), and long (60–160). During the presentation of visual stimuli, the 19–channel EEG was recorded with a sample rate of 512 Hz and cut-off frequencies of 0.1–50 Hz. The memory encoding process was analyzed with the event-related potential (ERP) and time-frequency (TF) methods for selected regions of interest (ROI) electrodes F3, F7, C3, P3, T3, and T5 in the 10–20 system corresponding to language processing brain areas. We compared ERP and TF data regarding the list length in the −100 ms to 700 ms time window. ROI electrodes T3, T5, and P3 indicated significantly different involvement of language processing areas under different list lengths by ERP observation. More lateralized regions (F7, T3) provided evidence for more pronounced differences in the encoding process than less lateralized regions (F3, C3). The analysis of TF revealed differences in theta, alpha, and beta wave bands in the F3 and P3 channels. Medium lists demonstrated higher differences from short and long lists, indicating a nonlinear trend in the involvement of language-processing regions.